Selected lssues Of the Imams Of Imam AL- Bazzai in the Book of Prayer from his Book of Fatwas AL- Bazaziyyah (Journal of the College of Education for Women, 2019)
The research included four topics: the definition of Imam al-Bazzazi, his scientific life, his sheikhs, his students, his writings, his death, and selected issues of his weight in the book of prayer. The Imam al-Bazazi is the son of Muhammad ibnShihabibn Yusuf. He is known as al-Khardizi al-Khawarizmi. The author did not adopt the definitions of language and terminology, and rarely mention the legal evidence adopted by the scholars in their opinions, and only to mention the views only, and the author, may God have mercy on him in his book on the sources of m The Prophet (peace and blessings of Allaah be upon him) said: "The Prophet (peace and blessings of Allaah be upon him) And fall down the order, the third issue, which is to leave the prayer deliberately committed to repentance and the judiciary